ANALYSIS OF THE METHODOLOGY FOR EVALUATING THE EFFECTIVENESS OF THE MECHANISM OF FINANCING THE ACTIVITIES OF AGROCLUSTERS - Mamadaliyev Qodirjon Qobuljonovich; Nematillayev Bekmirza (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article analyzes the mechanism of financing agricultural clusters from an economic point of view. It was carried out on the basis of the annual reports of the Khojaabad Fayz-M cotton-textile cluster operating in the Andijan region. The effectiveness of the financing mechanism for agricultural clusters has been assessed.